2020
DOI: 10.1093/jamia/ocaa305
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual considerations for using EHR-based activity logs to measure clinician burnout and its effects

Abstract: Electronic health records (EHR) use is often considered a significant contributor to clinician burnout. Informatics researchers often measure clinical workload using EHR-derived audit logs and use it for quantifying the contribution of EHR use to clinician burnout. However, translating clinician workload measured using EHR-based audit logs into a meaningful burnout metric requires an alignment with the conceptual and theoretical principles of burnout. In this perspective, we describe a systems-oriented concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…This consists of periodically conducting surveys and measurements of workers to "monitor" the organization's burnout levels and compare the scores of workers according to units, location, position, supervisor, etc. (e.g., [89]). The aim is basically to identify the appearance of the first symptoms, thus preventing the syndrome from becoming chronic.…”
mentioning
confidence: 99%
“…This consists of periodically conducting surveys and measurements of workers to "monitor" the organization's burnout levels and compare the scores of workers according to units, location, position, supervisor, etc. (e.g., [89]). The aim is basically to identify the appearance of the first symptoms, thus preventing the syndrome from becoming chronic.…”
mentioning
confidence: 99%
“…42,43 Lastly, task sequence may also indicate CIS-related documentation burden. 39 In this analysis, clinicians were more likely to switch from and to the same task at higher proportions compared with a different task following multitasking, with the exception of transcribing and log into EHR. While observed at lower frequencies, multitasking of medication reconciliation and transcribing was always succeeded by the same task.…”
Section: Discussionmentioning
confidence: 85%
“…Our analysis revealed that ED clinicians experienced 1.4 AE 0.6 task switches/min, 23 which intensified by 33.0% when multitasking. According to Kannampallil et al, 39 greater taskswitching is associated with increased cognitive resource expenditure; therefore, tasks that are performed frequently but exhibit short average duration, such as viewing patient list/schedule or viewing data, may indicate excessive taskswitching and documentation burden (►Table 2). Interestingly, these short duration tasks pertain to data retrieval and patient selection, 40,41 which are high-risk areas for medical errors especially if poor EHR design and usability are present.…”
Section: Discussionmentioning
confidence: 99%
“…Given the number of interventions aimed at combating EHR-related burnout in the published literature, our team conducted a rapid literature review on this topic [ 25 ]. From a review of 50 related articles published between 2014 and 2019, we found that the measurement of EHR burden needs to be performed both subjectively (eg, via surveys) and objectively (eg, using use data) [ 26 ]. We also identified that interventions to reduce EHR burnout were focused on four main aspects: enhancing and redesigning the interface of EHR screens, delivering tailored education and training to end users, improving communication, and providing additional support for administrative tasks [ 25 ].…”
Section: Building Our Physician Engagement Strategymentioning
confidence: 99%